Eksplorasi Kegiatan Praktikum IPA PGMI Selama Pandemi Covid-19 - Dita Purwinda Anggrella; Amining Rahmasiwi; Dwi Purbowati (Universitas Indraprasta PGRI Jakarta, 2021)
This study aims to explore student experiences in carrying out science practicum activities during online learning in covid-19 pandemic. This research is an exploratory research which analyzed in desriptive qualitative. The research population was the students of IAIN Surakarta. The sampling technique was purposive sampling, where the participants involved in this study were 80 students of PGMI IAIN Surakarta who studied science during the covid-19 pandemic in August 2020. Research data was taken through the distribution of online questionnaires using google form platform and interviews with lecturer. The results showed that science practicum activities during the COVID-19 pandemic were carried out through independent practice at home and recorded in video. The results showed 87.3% of students stated that the learning science process during the pandemic was ineffective due to the lack of lecturers' innovation in choosing appropriate learning strategies for practicum activities, 61.9% of students stated that there was a lack of learning resources including the availability of tools and materials, and 36.4% of students stated the lack of references used because they only had journal articles and internet pages. This study also discovered other findings related to the need for practicum learning resources for students, where 50.8% said they needed electronic media, 33.9% needed modules, and 7.6% needed textbooks as learning resources for practicum.